Phase and stress evolution in diamond microparticles during diamond-coated wire sawing of Si ingots. Issue 9 (February 2016) - Yang, Junting; Banerjee, Sriya; Wu, Junnan; Myung, Yoon; Rezvanian, Omid; Banerjee, Parag
Abstract Diamond microparticles undergo changes to their structure and stress state during diamond-coated wire sawing of Si ingots. This phenomenon is revealed using confocal, micro-Raman spectroscopy of diamond microparticles attached to wires which perform the sawing action. Post-wafer-sawed diamonds show the appearance of D (1350 cm−1 ) and G (1597 cm−1 ) bands of graphite besides the characteristic diamond T2g band at 1332 cm−1 . The graphitic phase extends inside the diamond to a depth of ~ 14 μm. The ratio of the intensities of D and G bands allows an estimate of the graphitic crystallite size. The grain size varies from 10 nm close to the surface to 53 nm near the graphite/diamond interface. On other diamonds, blue shifts in the T2g peak position are observed indicating the presence of compressive stress. The peak shifts (up to 3.6 cm−1 ) are anisotropic, i.e., along the direction of wire cutting, and are estimated to be 2.9 GPa. It is proposed that the cumulative effect of compressive stresses over multiple cutting events during the sawing process can lead to local graphitization of diamond particles, thus contributing to loss in cutting efficiency.